Long-term nitrogen and sulfur deposition increased root-associated pathogen diversity and changed mutualistic fungal diversity in a boreal forest. (April 2021) - Wu, Yingtong; Kwak, Jin-Hyeob; Karst, Justine; Ni, Ming; Yan, Yifan; Lv, Xiaofei; Xu, Jianming; Chang, Scott X.
Abstract: Anthropogenic nitrogen (N) and sulfur (S) deposition can change above- and belowground biodiversity, including root-associated fungi that are tightly linked to plant fitness. We investigated the effect of eleven years of N and S addition on the diversity of root-associated fungal pathogens and mutualists, including ectomycorrhizal fungi (EMF), dark septate endophytes (DSEs), and ericoid mycorrhizal fungi (ERM), in a broadleaf tree-dominated boreal forest using HiSeq sequencing of ITS2 amplicons of root fungal DNA. Long-term N and S addition increased the diversity of root-associated pathogens, notably the abundance of Venturia macularis, which causes aspen leaf and shoot blight, in the forest floor. Nitrogen addition increased the abundance of several N-sensitive EMF taxa and of EMF related to organic-N uptake from the soil, but had little effect on the overall abundance and diversity of EMF. Nitrogen and S addition did not affect the abundance and diversity of DSEs, but N addition decreased the Shannon diversity and evenness of ERM communities in the mineral soil. The changed diversity of root-associated fungal pathogens and mutualists suggests that long-term N and S addition will impact the host plant's capacity for nutrient acquisition and defense against pathogens in the broadleaf-dominated boreal forest. Highlights: N and S addition increased the diversity of root-associated fungal pathogens. N addition increased abundance of Venturia macularis, which causes aspen blight. N addition increased the relative abundance of N-sensitive ectomycorrhizal fungi. N addition decreased Shannon diversity and evenness of ericoid mycorrhizal fungi.